Motivating Mormons. Issue 2 (18th October 2014) - Curtis, Daniel; Cnaan, Ram A.; Evans, Van
<x xml:space="preserve">Abstract</x> Despite numerous studies on motivation for generosity, much remains unknown. Given that the lion's share of giving and volunteering is directed toward religious institutions, we aimed to test the motivation for the generosity of Mormons. Previous research has indicated that Mormons (Latter‐day Saints) volunteer and donate at much higher levels than other groups. This study examined how self‐reported motivations to volunteer explain the annual number of hours volunteered and the likelihood of donating toward various causes. We used thirty qualitative interviews with Latter‐day Saints to create a comprehensive questionnaire measuring the time spent engaged in various volunteer activities and whether or not the respondents donated to various causes. The questionnaire also asked respondents to rank how important twenty‐five different motivations were to their service or volunteering. We used factor analysis of the results on the twenty‐five motivation items to identify underlying variables behind volunteer motivations, and we used the scores on the five resulting factors in multiple regression analyses to predict volunteer hours and logistic regression analyses to predict the likelihood of making donations. Different types of motivations predicted different types of volunteering and charitable giving. Theological motivations had the broadest impact and predicted religious volunteering, social volunteering to benefit church members, social volunteering through the church to benefit the community, religious donations, and donations toward social causes made through the church. After inserting control variables into our models, we found that none of the five types of motivations predicted secular volunteering or secular charitable giving. We conclude with managerial and conceptual implications of these and other results.